Analisis Hubungan Manajemen Ketersediaan SDM Perawat dengan Tingkat Beban Kerja Perawat - Luthfia Cahnaya Manangin; Sitti Rahma; Moh. Nisyar Sy. Abd. Azis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the relationship between nurse human resource availability management and nurse workload levels in the inpatient ward of Kotamobagu City Hospital. A cross-sectional method with proportionate stratified random sampling was used, with a sample of 56 nurses. The results showed a relationship between nurse human resource availability management and nurse workload levels (p-value = 0.000). In conclusion, a relationship exists between nurse human resource availability management and nurse workload levels at Kotamobagu City Hospital. Keywords: Human Resource Availability Management, Nurses, Inpatient Wards, Workload Level